Truth, Error, and Criminal Law An Essay in Legal Epistemology - Laudan, Larry (Cambridge University Press, 2013)
After puzzling over the relevant passages, he replied candidly: “No.” This book dates from that conversation. Probably as much to get me out of his hair as anything else, Brian put me onto LexisNexis, that wonderful repository of all things legal on the Internet. I started reading other Supreme Court cases discussing reasonable doubt, hoping that would set me straight. It did not. This book is the end product of my quest for an answer to that initial and seemingly innocuous question. As these things always do, my puzzle about reasonable doubt mushroomed into worries about a plethora of epistemic notions (the benefit of the doubt, the presumption of innocence, the burden of proof, relevance, and reliability) widely used by the judiciary and academic lawyers alike